A nodal-based extrinsic cohesive/contact model for interfacial debonding analyses in composite structures. (15th April 2019) - Chen, Shunhua; Mitsume, Naoto; Gao, Wei; Yamada, Tomonori; Zang, Mengyan; Yoshimura, Shinobu
Highlights: A novel nodal-based extrinsic cohesive zone model is proposed for debonding analyses. The proposed model is computationally more efficient than the widely-used intrinsic model. The proposed model is able to address the time-continuity problem arising in the conventional extrinsic model. A simple but efficient approach is proposed to facilitate adaptive nodal duplication. The proposed model is coupled with a tributary node-to-segment contact algorithm. Abstract: Interfacial debonding is one of the major failure patterns in composite structures. In this work, a nodal-based extrinsic cohesive/contact model is proposed for the purpose of efficient and accurate debonding analyses. On one hand, unlike the commonly used intrinsic cohesive zone model, finite element nodes in the proposed model are adaptively duplicated when and where needed along with the advance of debonding, and thus to save computational cost. On the other hand, a fracture criterion, which is performed directly at nodes, is proposed to guarantee nodal forces to be continuous before and after nodal duplication. In doing so, the new model is capable of addressing the so-called time continuity problem existing in the conventional extrinsic model in an efficient way. In addition, a simple but efficient detection technique is developed to facilitate adaptive nodal duplication. The developed cohesive zone model is then coupled with a tributary node-to-segment contact algorithm to achieve a smooth transition from cohesive failure to contact sliding. Several numerical examples are performed to validate the efficiency and effectiveness of the proposed model.